Recent trends in (under)treatment of hypercholesterolaemia in the Netherlands - Mantel-Teeuwisse, Aukje K (Blackwell Science Inc, 2004)
AIM: To assess recent trends in undertreatment of hypercholesterolaemia (1998–2002). METHODS: Data were obtained from the third cross-sectional examination of the Monitoring Project on Risk Factors for Chronic Diseases (n = 4878; age 31–70 years), conducted in the Netherlands. Treatment eligibility was established according to Dutch guidelines. Data from the second examination (1993–1997) were used to assess time trends. The association between demographic variables, cardiovascular disease risk factors, drug use and lipid-lowering medication was assessed using multivariable logistic regression. RESULTS: Overall, 45.9%[95% confidence interval (CI) 41.4, 50.4] of respondents eligible for treatment were treated, and 17.4% (95% CI 13.9, 20.9) were both treated and controlled (1998–2002). Treatment increased significantly after 1995, showed a slight decrease in subsequent years until 2000, when treatment increased again. Subgroups less frequently treated for primary prevention included among others males [odds ratio (OR) = 0.08; 95% CI 0.03, 0.21], younger patients (OR = 0.93 per year; 95% CI 0.88, 0.98), diabetics (OR = 0.19; 95% CI 0.07, 0.56), untreated hypertensives (OR = 0.21; 95% CI 0.09, 0.49) and current smokers (OR = 0.09; 95% CI 0.03, 0.25). In secondary prevention, patients with a history of stroke were less likely to receive treatment (OR = 0.41; 95% CI 0.18, 0.94) compared with patients with a history of ischaemic heart disease. CONCLUSIONS: Treatment of hypercholesterolaemia has steadily increased over the past 10 years in the Netherlands. However, at present still less than one out of two eligible for treatment is treated, and only about one out of six is both treated and controlled.